Global value relations and local labour control regimes in rice farming in Uganda and Tanzania. (March 2020) - Greco, Elisa
This study presents evidence on the organisation of farm work in rice farming areas in Uganda and Tanzania, where farms of different scale co-exist, drawing on the same pool of workers. Here, local labour regimes have been rapidly reorganised following the creation and expansion plans of mega-farms after the global financial crisis of 2007/2008, characterised as land grabs. The synchronic comparison of two rice mega-farms is based on the history of relations of production in rice farming areas in the region. With post-crisis global restructuring, shifting global value relations have driven the reorganisation of control within the labour process in frontiers of capitalist accumulation. This article argues that local labour process and farm labour regimes are important elements in the process of mediation with global value relations in the study areas. Labour control within the labour process and local labour regimes across farm scale are at the core of the additional reasons leading local workers to see employment on mega-farms undesirable, compared to gang work on local farms of different size. Work on mega-farms, alongside its highly exploitative character, is undesirable for workers because of the tight system of disciplining at the basis of labour control, which creates conflicts with the social reproduction system. The devalorisation and exploitation of labour is enabled by disciplining and control over workers in the production process.